2022
DOI: 10.7759/cureus.23401
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Surface Diseases in Patients With Diabetes

Abstract: Purpose Diabetes is a major cause of ocular morbidity as multiple mechanisms play a role in inducing inflammatory changes in the eye. Diabetic retinopathy is the most common complication and is well-documented. However, in the era of modern medicine, attention is also being focused on ocular surface changes in diabetes. Therefore, this study aimed to determine the association between diabetes and ocular surface diseases. Materials and Methods This is a cross-sectional study exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
(35 reference statements)
0
8
2
Order By: Relevance
“…This was comparable to another study by Didenko et al 17 where the prevalence of corneal ulcer in T2DM was 6.6%, recurrent corneal erosion was 8.2% and punctate keratopathy was 21.3%. In our investigation, we found that 26.9% of T2DM patients had reduced corneal sensations, which was higher than the 12% prevalence found in the study by Naik K et al 18 In our investigation, we discovered that the prevalence of dry eye was 14.3% in T1DM, 32% in T2DM, 35% in hypothyroidism and highest (55.6%) in GO. Naik k et al 18 carried out a similar investigation with T1DM and T2DM, wherein dry eye was shown to be more common in T2DM (66 out of 160 cases) than in T1DM (15 out of 160 cases).…”
Section: Discussioncontrasting
confidence: 60%
“…This was comparable to another study by Didenko et al 17 where the prevalence of corneal ulcer in T2DM was 6.6%, recurrent corneal erosion was 8.2% and punctate keratopathy was 21.3%. In our investigation, we found that 26.9% of T2DM patients had reduced corneal sensations, which was higher than the 12% prevalence found in the study by Naik K et al 18 In our investigation, we discovered that the prevalence of dry eye was 14.3% in T1DM, 32% in T2DM, 35% in hypothyroidism and highest (55.6%) in GO. Naik k et al 18 carried out a similar investigation with T1DM and T2DM, wherein dry eye was shown to be more common in T2DM (66 out of 160 cases) than in T1DM (15 out of 160 cases).…”
Section: Discussioncontrasting
confidence: 60%
“…Chronic hyperglycemia can significantly impact various ocular surface components, including the corneal epithelium, corneal nerves, tear film, endothelium, and conjunctiva [ 84 ]. Abnormalities in the cornea (delayed epithelial wound healing, edema, corneal erosions, neuropathy, decreased sensitivity) and tear film changes have been reported [ 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. A healthy cornea depends on the appropriate functioning and communication of epithelial cells, sensory neurons, and resident immune cells, and diabetes disrupts their interaction and cooperation.…”
Section: The Impact Of Diabetes and Dr On Ocular Surface And Tear Pro...mentioning
confidence: 99%
“…In the retina, DM induces neovascularization and microvascular damage, causing retinopathy [ 9 , 10 , 11 , 12 ], which is one of the leading causes of vision loss. DM is known to cause ocular surface changes, leading to a higher incidence of ocular surface disease, including dry eye, in diabetic patients [ 13 , 14 , 15 , 16 ]. Additionally, DM is also associated with other ophthalmic disorders, such as glaucoma [ 17 , 18 ] and cataracts [ 10 , 19 ].…”
Section: Introductionmentioning
confidence: 99%